Analysis of the Microbial Community Structure during Brewing of Sichuan Xiaoqu Baijiu. (3rd July 2019) - Wang, Ming-Yao; Zhao, Qing-Song; Chang Su; Yang, Jian-Gang
Abstract: Chinese baijiu is produced using a unique brewing method, and few studies have examined changes in microbial communities during baijiu fermentation. In this study, changes were evaluated in the microbial communities of Sichuan Xiaoqu baijiu fermented grains using high-throughput sequencing. The bacterial community mainly consisted of Enhydrobacter, Acinetobacter, Leuconostoc, Escherichia-Shigella, Weissella, and Klebsiella . Klebsiella was the dominant microorganism, accounting for >75% of the bacteria on days 1, 3, 5, and 7 of fermentation. Fungal communities consisted mainly of Saccharomycetales and Rhizopus oryzae . The abundance of R. oryzae was 88% on day 1 but decreased rapidly to 4% on day 5, with 0% R. oryzae on day 7. In contrast, Saccharomycetales abundance was only 10% on day 1 but was much higher on days 5 and 7 at 99% and 100%, respectively. Acidity increased, and pH decreased during fermentation. Additionally, the temperature and reducing sugar content first increased and then decreased, whereas the ethanol and water content increased. Finally, Saccharomycetales was strongly correlated with reducing sugars, suggesting it may be a functional microorganism during fermentation. These data provide some insights into the functional microorganisms involved in the fermentation process, enabling a deeper understanding of Xiaoqu liquor.